A Comparative Analysis of Experimental Learning Approach and Traditional Teacher Professional Development Programs - Osias Kit T. Kilag; Marsha Heyrosa-Malbas; Marivic U. Sebial; Jeraldine M. Mayol (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This quantitative research study aimed to compare the effectiveness of experimental learning approaches and traditional professional development programs in improving the learning outcomes of teachers. The study was conducted with 40 teachers from two private schools in the Philippines. Participants were randomly assigned to either the experimental learning group or the traditional professional development group. Data were collected through a pretest-posttest questionnaire and a satisfaction survey. The pretest-posttest questionnaire consisted of 20 multiple-choice questions designed to assess the participants' knowledge, skills, and understanding of the latest teaching methodologies and technologies. The satisfaction survey consisted of 10 items designed to measure the participants' satisfaction with the content, structure, and delivery of the program. Results showed that the experimental learning group had higher mean scores in both the pretest and posttest questionnaires, indicating that the hands-on, real-life experiences provided in the workshop facilitated the development of new skills and knowledge. The experimental learning group also had a higher mean score in the satisfaction survey, indicating a higher level of satisfaction and motivation towards the professional development program. These findings are consistent with previous research that has highlighted the effectiveness of experimental learning approaches in enhancing the professional development of teachers. The study suggests that schools should consider incorporating experimental learning approaches into their professional development programs to enhance the skills and knowledge of their teachers. Limitations of the study include the small sample size and the fact that the study was conducted in only two private schools in the Philippines. Future research could be conducted with a larger and more diverse sample to further examine the effectiveness of experimental learning approaches in teacher professional development programs. Overall, this study provides valuable insights into the effectiveness of experimental learning approaches in teacher professional development programs.